Pengaruh Digital Marketing Terhadap Loyalitas Konsumen Melalui Brand Engagement Pada Shopee Indonesia - Adinda Cahya Kamilla Firdauzi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Competition in Indonesia’s e-commerce industry has intensified, marked by the growing dominance of Tokopedia and TikTok Shop, which has begun to pressure Shopee’s market position. The decline in website visits and the decreasing frequency of user transactions indicate that consumer loyalty toward Shopee is weakening. These conditions highlight the importance of digital marketing strategies and brand engagement in retaining customers amid a rapidly evolving market landscape. This study aims to analyze the influence of digital marketing on consumer loyalty, with brand engagement serving as a mediating variable among Shopee users in Indonesia. A quantitative research method was employed by distributing questionnaires to 200 active Shopee users. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results show that digital marketing has a positive and significant effect on brand engagement (t = 8.706; p = 0.000). Brand engagement also demonstrates a strong and significant influence on consumer loyalty (t = 17.376; p = 0.000). In addition, digital marketing exerts a direct influence on loyalty, although with a lower level of significance (t = 2.238; p = 0.025). The study further reveals that the indirect effect of digital marketing on loyalty through brand engagement is significant (t = 7.529; p = 0.000), confirming the mediating role of brand engagement. Overall, the findings indicate that the effectiveness of digital marketing in enhancing consumer loyalty relies heavily on the ability to create digital experiences that are relevant, interactive, and value-driven for Shopee users. These insights provide strategic implications for strengthening digital marketing practices and fostering long-term customer relationships in the Indonesian e-commerce sector.